The verbalization of fear emotion by means of paralinguistic phraseologisms in the Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article deals with the fear emotion and the peculiarities of its verbalization by means of paralinguistic phraseologisms in the Ukrainian language based on general principles of psyche functioning, especially of emotional sphere structure analysis, to the conception of language mentality as a mode of interpretation of the world, and paralinguistic phraseologisms as their speech product. The author investigates the creation of certain set expressions taking into account national cultural peculiarities of linguistic behaviour.
Keywords: emotion; paralinguistic phraseologism; physiological changes; linguoemotional picture of the world